Effect of altered reproductive function and lowered testosterone levels on bone density in male endurance athletes - Bennell, K. L.; Brukner, P. D.; Malcolm, S. A. (British Journal of Sports Medicine, 1996)
It is apparent that bone density in male athletes can be reduced without a concomitant decrease in testosterone, suggesting that bone density and testosterone concentrations in the normal range are not closely related in male athletes. Further research is necessary to monitor concurrent changes in bone density and testosterone over a period of time in exercising males. In any case, the effect of exercise on the male reproductive system does not appear as extreme as that which can occur in female athletes, and any impact on bone density is not nearly as evident. These results imply that factors apart from testosterone concentrations must be responsible for the observed osteopenia in some male athletes. Many factors have the potential to adversely affect bone density, independently of alterations in reproductive function. These include low calcium intake, energy deficit, weight loss, psychological stress, and low body fat, all of which may be associated with intense endurance training. Future research investigating skeletal health in male athletes should include a thorough assessment of reproductive function in addition to these other factors.